Plant Metabolism and Biotechnology 2011
DOI: 10.1002/9781119991311.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Nitrogen Fixation

Abstract: Nitrogen for all living organisms ultimately comes from atmospheric dinitrogen (N 2 ). Biological nitrogen fixation is a reaction whereby N 2 is reduced to ammonium (NH 3 ) by a special enzymatic system, of which the primary enzyme is the nitrogenase complex. The nitrogenase system is found in various prokaryotes (diazotrophic bacteria or diazotrophs). They can be grouped into two categories: one is the group of free-living nitrogen fixers which inhabit the soil, fresh water and seawater, and the other is a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Root nodule symbioses are only found in plants of a monophyletic clade often referred to as “FaFaCuRo” ( Fabales , Fagales , Curcubitales , and Rosales ) but are incredibly diverse in modes of infection by rhizobia or Frankia , nodule anatomy, and metabolism [3235]. Associations between legumes and rhizobia are so efficient that legumes are found in a wide range of environments across the globe and used in nearly all cropping systems [36].…”
Section: Introductionmentioning
confidence: 99%
“…Root nodule symbioses are only found in plants of a monophyletic clade often referred to as “FaFaCuRo” ( Fabales , Fagales , Curcubitales , and Rosales ) but are incredibly diverse in modes of infection by rhizobia or Frankia , nodule anatomy, and metabolism [3235]. Associations between legumes and rhizobia are so efficient that legumes are found in a wide range of environments across the globe and used in nearly all cropping systems [36].…”
Section: Introductionmentioning
confidence: 99%
“…In symbiosomes, they further differentiate into a symbiosis‐specific form, the bacteroid, and then develop N 2 ‐fixing ability. Housing within the nodule cells and differentiation into bacteroids are essential for rhizobial N 2 fixation; therefore, bacteroid differentiation and N 2 ‐fixing activity are under strict control through interactions between host plant cells and endosymbionts (reviewed in Kouchi, ). The host‐determined Fix – mutants, which are able to form morphologically normal nodules with endosymbiotic bacteria but are defective in nitrogen fixation, are the most useful tool with which to identify the legume genes involved in such interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that among the sulfate fertilizers tested, the applied ammonium sulfate significantly increased the number of copies of the nif H gene in soil compared to soils fertilized with potassium sulfate or magnesium sulfate only ( Table 3 ). This observation is difficult to explain because sulfur is an essential component of nitrogenase, and this enzyme’s biosynthesis is based on high levels of imported sulfate [ 88 , 89 ]. The aforementioned changes in the content of water-soluble organic carbon fractions, which were not related to changes in the number of molecular markers of bacteria, suggest that there were no significant changes in the number of bacteria, but the microbial utilization of labile carbon nutrients in soil fertilized especially with sulfates was more intensive.…”
Section: Resultsmentioning
confidence: 99%